2021
DOI: 10.1002/jnr.24975
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the corticoreticular pathway from cortex‐wide anterograde axonal tracing in the mouse

Abstract: The corticoreticular pathway (CRP) has been implicated as an important mediator of motor recovery and rehabilitation after central nervous system damage. However, its origins, trajectory and laterality are not well understood. This study mapped the mouse CRP in comparison with the corticospinal tract (CST). We systematically searched the Allen Mouse Brain Connectivity Atlas (© 2011 Allen Institute for Brain Science) for experiments that used anterograde tracer injections into the right isocortex in mice. For e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 69 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…Unlike SMA and PMd, SFG9m is not typically considered a motor region, but this finding adds to a growing body of evidence that SFG9m may indeed be a novel motor area, or at least highly relevant to walking function. 28,29,59,60 For example, the medial prefrontal cortex (including SFG9m) was recently found to be a major origin of a key descending projection for gross motor functions like walking (the cortico-reticulo-spinal pathway). 59,60 The current study cannot determine whether SFG9m exerted any direct effects on walking through the cortico-reticulo-spinal pathway and/or indirect effects via connections with established motor regions of the cortex (M1-LL, SMA, PMd).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike SMA and PMd, SFG9m is not typically considered a motor region, but this finding adds to a growing body of evidence that SFG9m may indeed be a novel motor area, or at least highly relevant to walking function. 28,29,59,60 For example, the medial prefrontal cortex (including SFG9m) was recently found to be a major origin of a key descending projection for gross motor functions like walking (the cortico-reticulo-spinal pathway). 59,60 The current study cannot determine whether SFG9m exerted any direct effects on walking through the cortico-reticulo-spinal pathway and/or indirect effects via connections with established motor regions of the cortex (M1-LL, SMA, PMd).…”
Section: Discussionmentioning
confidence: 99%
“…28,29,59,60 For example, the medial prefrontal cortex (including SFG9m) was recently found to be a major origin of a key descending projection for gross motor functions like walking (the cortico-reticulo-spinal pathway). 59,60 The current study cannot determine whether SFG9m exerted any direct effects on walking through the cortico-reticulo-spinal pathway and/or indirect effects via connections with established motor regions of the cortex (M1-LL, SMA, PMd). Given the correlational nature of this result, it is also possible that SFG9m did not exert any effects on walking (non-causal/confounded association) or that faster walking somehow led to greater SFG9m activation (reverse causality).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of relatively few anatomical correlates of finger force in the current analysis, may be methodological constrains of VLSM, which cannot detect lesion-symptom relationship outside the minimal overlap region, which included only regions within the core of MCA vascular territory which included the CST but only small part of the CRP. Additionally, CST descends in a much smaller area relative to the CRP, thus is far more vulnerable to focal damage 64,65 (compare the CST and CRP on the first and third rows, respectively). The partial dissociation of neural mechanisms controlling finger individuation and strength (depicted in Figures 3F and 4B), is reflected also in the inverse anatomical patterns of individuation and strength in flexion and extension (much more flexion-selective voxels in VLSM analysis of individuation capacity, in contrast to the existence of extension-selective but no flexion-selective brain voxels in the VLSM analysis of finger strength; Table 4).…”
Section: Different Neural Mediation Of Finger Strength and Individuationmentioning
confidence: 99%
“…Sensorimotor Area Tract Template (SMATT) 64 ; the cortico-reticular pathway (CRP) based on a recently published template 65 ; trajectories of association tracts based on the XTRACT atlas and template 82 . Only voxels belonging to clusters of more than 5 adjacent significant voxels are reported.…”
Section: Supplementary Information Experiments 1 -Individuation Index...mentioning
confidence: 99%
“…[ 124 ] While long‐term follow‐up studies demonstrated that it was of no avail for gait disturbance, neither reduced the incidence of complications related to cognitive or emotional disorders, such as dementia and depression. [ 125 ] Notably, although the dyskinesia of PD roots in the inordinate inhibition of subcortical structures (basal ganglion, thalamus) to the motor cortex, downstream pathways including internal capsule, brain stem, and spinal cord cooperate intimately to accomplish motor reflex, [ 126 ] and the motor coordination depends on cortex‐cerebellum connection for repeat comparison and adjustment between cortical launch and downstream execution. [ 127 ] Moreover, there are intricate projections from basal ganglion to brain stem, which may account for the gait disturbance of PD.…”
Section: Challenges and Perspectives For Clinical Translation Of Tspcimentioning
confidence: 99%